2019
DOI: 10.4041/kjod.2019.49.6.360
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of midpalatal suture expansion by miniscrew-assisted rapid palatal expansion in young adults: A preliminary study

Abstract: ObjectiveWe sought to determine the predictors of midpalatal suture expansion by miniscrew-assisted rapid palatal expansion (MARPE) in young adults.MethodsThe following variables were selected as possible predictors: chronological age, palate length and depth, midpalatal suture maturation (MPSM) stage, midpalatal suture density (MPSD) ratio, the sella-nasion (SN)-mandibular plane (MP) angle as an indicator of the vertical skeletal pattern, and the point A-nasion-point B (ANB) angle for anteroposterior skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 27 publications
(41 reference statements)
3
30
2
Order By: Relevance
“…The mean skeletal expansion ranged from 1.11 mm to 4.5 mm and was statistically significant in all five articles ( 28 , 29 , 31 , 32 , 34 ) where the p-value was calculated. One study differentiated between a midpalatal suture separation group and a non-separation group and reported results for both groups separately and combined ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean skeletal expansion ranged from 1.11 mm to 4.5 mm and was statistically significant in all five articles ( 28 , 29 , 31 , 32 , 34 ) where the p-value was calculated. One study differentiated between a midpalatal suture separation group and a non-separation group and reported results for both groups separately and combined ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Different expansion protocols were used across the studies. The mean duration of expansion in those studies with a rapid expansion protocol ranged from 20 to 35 days ( 30 , 32 , 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because MARPE opens the midpalatal suture, inducing bone formation between the separated sutures that ensures maintenance of the maxillary arch width even after the molars are lingually uprighted due to the intrinsic buccolingual inclination of the brackets during presurgical orthodontics. [18][19][20]26 In several previous studies, [27][28][29] skeletal tissues have been reported to be stable at 6 months after orthognathic surgery. Normally, debonding in cases undergoing presurgical orthodontic treatment is performed within 6 months of surgery.…”
Section: Discussionmentioning
confidence: 98%
“…This is because MARPE opens the midpalatal suture, inducing bone formation between the separated sutures that ensures maintenance of the maxillary arch width even after the molars are lingually uprighted due to the intrinsic buccolingual inclination of the brackets during presurgical orthodontics. 18 - 20 , 26 …”
Section: Discussionmentioning
confidence: 99%